The rural and urban community perceptions of ecosystem goods and services in the semi-arid reservoirs landscape - Osório de Sousa, Lívia Maria; Barbosa de Melo, Dalescka; Marques Rocha Ferreira, Lucianna; Molozzi, Joseline (Ethnobiology and Conservation, 2024)
Ecosystem goods and services (EGS) are the contributions that ecosystems provide to human well-being. The reservoir landscape, an artificial ecosystem, offers a wide range of ecological and socioeconomic functions for local populations, such as potable water, irrigation, and plants for food purposes. This study aimed to assess the perception of EGS provided by the reservoir landscapes of rural and urban populations. Research was conducted with residents around reservoirs in the Paraiba Basin of Brazil, specifically in the cities of Camalaú and Boqueirão. Socioeconomic information and population perceptions were obtained using semi-structured forms and participatory mapping, respectively. Based on analyses using PERMANOVA and Mann-Whitney statistical tests, it was found that rural people and men perceived and cited a higher number of EGS. Responses varied with different education levels (Illiterate, Primary School Incomplete, Primary School Complete, High School Incomplete, High School Complete, and University Degree Complete), with provisioning services being more easily perceived and mentioned by the interviewees. People in direct contact with the natural environment were more likely to perceive EGS than those without such contact. However, the importance of EGS was recognised by both rural and urban populations, as these services are essential for their well-being. Perceptions of riverside populations are important for conservation efforts because they provide valuable information about ecosystems based on their experiences within these ecological systems.